PSYCHOLOGICAL EFFECT OF COMMUNICATION SKILLS ON CUSTOMER RETENTION: EVIDENCE FROM SUPPLY CHAIN PROCESS OF INDONESIAN ELECTRONIC COMPANIES - Martey, EdwardMarkwei; Brew, Yaw; Frempong, Joseph (International Journal of Supply Chain Management, 2020)
Purpose of this study is to investigate the psychological effect of communication skills on customer retention (CR) with mediating role of customer satisfaction (CS) and customer loyalty in supply chain process of electronic companies. Number of studies studied the phenomena of CR; however, it is not studied with the help of psychological effect of communication skills. Moreover, the supply chain procedure of electronic companies is not discussed by the previous studies. Hence, this study is an attempt to fill this literature gap by examining the relationship between psychological effect of communication skills, CS, customer loyalty and CR to investigate supply chain process. This study focused on electronic companies of Indonesia. Therefore, a survey was carried out among these companies. Data were obtained from the customers of Indonesian electronic companies. 600 questionnaires were distributed among the customers. It is evident from the results that psychological effect of communication skills has important contribution to the CR to enhance supply chain process. Positive psychological effect of communication skills has the ability to increase CR, however, negative psychological effect of communication skills has the ability to decrease CR.